Evaluation of Physicochemical Properties and Exopolysaccharides Production of Single Culture and Mixed Culture in Set Yoghurt - Heldy Oktavia; Lilik Eka Radiati; Djalal Rosyidi (Indonesian Journal of Environment and Sustainable Development, 2016)
The Rheology of yogurt was influenced by the dry matter of milk and yogurt cultures. The purpose of this research was to determine the effect of using single culture (L. bulgaricus, S. thermophillus) and mixed culture (L. bulgaricus and S. thermophillus), (S. thermophillus, L. bulgaricus and Bifidobacterium)as much as 3% for evaluation of physicochemical properties in set yoghurt such as pH value, acidity content, viscosity and syneresis, also to know total exopolysaccharides (EPS) production, total lactic acid bacteria (LAB) and microstructure of set yoghurt storage at refrigerator temperature (1 day, 2 and 3 days). The method of this research on first step was Randomized Completely Design, the variables measured on first step were pH content, acidity content, viscocity, and syneresis with 3 times replication. On second step used Randomized Completely Nested Design (3x4) with 3 times replication variables measured were pH stored, total lactic acid bacteria and total EPS production. The best treatment from second step continued testing of the microstucture with the aim of identifying structure components in set yoghurt. The conclusion on first step this research could decrease of pH value, increase the acidity, viscosity and inhibit syneresis set yogurt. On second step gave has decline in the average total LAB 1 log (CFU / ml) in set yogurt and has increasing of total exopolysaccharide production from each type of culture during.Keywords : Bifidobacterium, fermented milk, Lactabacillus, Streptococcus